Tragedy, Euripides, Melodrama: Hamartia, Medea, Liminality - Caraher, Brian G. (Amaltea. Revista de Mitocrítica, 2013)
Este artículo estudia las dimensiones sociohistóricas y las implicaciones culturales y teatrales del tratamiento que Eurípides da al mito de Medea. Eurípides da voz a las víctimas del aventurerismo, de las agresiones y de las traiciones cometidas en nombre de la ‘razón’ y del ‘estado’ o el ‘gobierno’. Medea es una de las fuerzas míticas más potentes a las que Eurípides dio voz, al transformar en melodrama la inquietante liminalidad del orden social y cultural de la tragedia. El gobierno social se enfrenta a un choque apocalíptico contra su orden y contra las formas de interpretación emocional, racional y social a su alcance. Los melodramas de horror de Eurípides teatralizan la violación de las categorías racionales y aceleran la liminalidad de la visión trágica del orden racional. Asimismo, se compara la dramaturgia de la Medea de Eurípides con las reglas de la tragedia griega y se examina a la luz de otras adaptaciones del mito, tanto antiguas como contemporáneas, a fin de desvelar cómo la obra transgrede la visión del gobierno social propia de la tragedia.AbstractThis article examines socio-historical dimensions and cultural and dramaturgic implications of the Greek playwright Euripides’ treatment of the myth of Medea. Euripides gives voice to victims of adventurism, aggression and betrayal in the name of ‘reason’ and the ‘state’ or ‘polity.’ Medea constitutes one of the most powerful mythic forces to which he gave such voice by melodramatizing the disturbing liminality of Greek tragedy’s perceived social and cultural order. The social polity is confronted by an apocalyptic shock to its order and its available modes of emotional, rational and social interpretation. Euripidean melodramas of horror dramatize the violation of rational categories and precipitate an abject liminality of the tragic vision of rational order. The dramaturgy of Euripides’ Medea is contrasted with the norms of Greek tragedy and examined in comparison with other adaptations — both ancient and contemporary — of the myth of Medea, in order to unfold the play’s transgression of a tragic vision of the social polity.
Keywords: Dramaturgy; Euripides; liminality; Medea; melodrama; preternatural powers; social polity; tragedy.